Glucose Intolerance after a Recent History of Gestational Diabetes Based on the 2013 WHO Criteria - Benhalima, Katrien (PLoS One, 2016)
AIMS: Uncertainty exists on the prevalence of glucose intolerance in women with a recent diagnosis of gestational diabetes (GDM) based on a two-step screening strategy and the 2013 World Health Organization (WHO) criteria. Our aim was to evaluate the uptake of postpartum screening, the prevalence and the risk factors for glucose intolerance in women with a recent history of GDM. METHODS: Retrospective analysis of the medical records of women with a recent history of GDM diagnosed in a universal two-step screening strategy with the 2013 WHO criteria. All women with a history of GDM are advised to undergo a 75g oral glucose tolerance test (OGTT) around 12 weeks postpartum. Indices of insulin sensitivity (the Matsuda index and the reciprocal of the homeostasis model assessment of insulin resistance, 1/HOMA-IR) and an index of beta-cell function, the Insulin Secretion-Sensitivity Index-2 (ISSI-2) were calculated based on the OGTT postpartum. Multivariable logistic regression was used to adjust for confounders such as age, BMI, ethnicity and breastfeeding. RESULTS: Of the 191 women with GDM, 29.3% (56) did not attend the scheduled postpartum OGTT. These women had a higher BMI (28.6 ±6.8 vs. 26.2 ± 5.6, p = 0.015), were more often from an ethnic minority (EM) background (41.1% vs. 25.2%, p = 0.029) and smoked more often during pregnancy (14.3% vs. 2.2%, p = 0.001) than women who attended the OGTT postpartum. Of all women (135) who received an OGTT postpartum, 42.2% (57) had prediabetes (11.9% impaired fasting glucose, 24.4% impaired glucose tolerance and 5.9% both impaired fasting and impaired glucose tolerance) and 1.5% (2) had overt diabetes. Compared to women with a normal OGTT postpartum, women with glucose intolerance were older (32.5±4.3 vs. 30.8±4.8 years, p = 0.049), were more often obese (34.5% vs. 17.3%, p = 0.023), were more often from an EM background (33.9% vs. 18.4%, p = 0.040), less often breastfed (69.5% vs. 84.2%, p = 0.041) and had more often an abnormal fasting glycaemia at the time of the OGTT in pregnancy (55.6% vs. 37.3%, p = 0.040). In the multivariable logistic regression, an EM background [OR = 2.76 (1.15–6.62), p = 0.023] and the HbA1c level at the time of the OGTT in pregnancy [OR = 4.78 (1.19–19.20), p = 0.028] remained significant predictors for glucose intolerance postpartum. Women with glucose intolerance postpartum had a similar insulin sensitivity [Matsuda index 0.656 (0.386–1.224) vs. 0.778 (0.532–1.067), p = 0.709; 1/HOMA-IR 0.004 (0.002–0.009) vs. (0.004–0.003–0.007), p = 0.384] but a lower beta-cell function compared to women with a normal OGTT postpartum, remaining significant after adjustment for confounders [ISSI-2 1.6 (1.2–2.1) vs. 1.9 (1.7–2.4),p = 0.002]. CONCLUSIONS: Glucose intolerance is very frequent in early postpartum in women with GDM based on the 2013 WHO criteria in a two-step screening strategy and these women have an impaired beta-cell function. Nearly one third of women did not attend the scheduled OGTT postpartum and these women have an adverse risk profile. More efforts are needed to engage and stimulate women with GDM to attend the postpartum OGTT.